Mental Health Preventive Strategies - Marques, Adilson; Gaspar de Matos, Margarida; Sarmento, Hugo (IntechOpen, 2023)
Worldwide, there is a high prevalence of mental health problems such as depression and anxiety. Mental health problems can affect all people regardless of their sociodemographic characteristics. This means that anyone is likely to have some form of mental health problem. The effects of mental health problems can be so devastating that they lead to suicide in many cases. For this reason, preventive measures to avoid mental health problems are important. Among the strategies used for the prevention and treatment of mental health problems, the practice of physical activity, good levels of physical fitness, quality leisure time, socialization (especially in older adults), the use of counseling whenever there is a change in mental health, religiosity and contemplation of the divine, psychological support, and professional guidance stand out. This book presents different strategies that can be used to promote good mental health.